Answer:
a = -1 and
b = 10
Explanation:
Given:
h(x) = (x – 1)³ + 10
h(x) = (g compose f)(x).
f(x) = x + a and
g(x) = x³ + b
To find:
The values of a and b = ?
Solution:
First of all, let us have a look at the composite functions.
(g compose f)(x) means we replace the value of
with
in the function
.
We know that:
and
![f(x) = x + a](https://img.qammunity.org/2021/formulas/mathematics/high-school/97no8tsaxr2vtcf7g2ywlm4qfosxbdagts.png)
Let us find (g compose f)(x) by replacing
with
![x+a](https://img.qammunity.org/2021/formulas/mathematics/high-school/6gybpbnxqcfhatjzmiyf6ypk45l1q2iczk.png)
![(g\ compose\ f)(x) = (x+a)^3+b](https://img.qammunity.org/2021/formulas/mathematics/high-school/vtjyfrdcmqzgyqqkdqxx7qmmgvpd1l9qu8.png)
Also, h(x) = (g compose f)(x) = (x – 1)³ + 10
Therefore,
![(x - 1)^3 + 10 = (x+a)^3+b](https://img.qammunity.org/2021/formulas/mathematics/high-school/ecz15q80cvd9qs404qxzrbdgqkr8hy4ik2.png)
Comparing the corresponding elements of the above expressions:
we get a = -1 and
b = 10